Students’ Digital Identities in English as a Foreign Language (EFL) Creative Writing in Indonesia - Dewi Widyastuti; Catharina Brameswari (Celt: A Journal of Culture, English Language Teaching and Literature, 2026)
This research highlights how the students in the English Letters Department of a private university in Yogyakarta, Indonesia, express their digital identities in English as a Foreign Language (EFL) Creative Writing. Even though digital platforms have been widely discussed as a medium for identity expressions and construction, few studies have specifically examined digital identity construction through EFFL creative writing on digital platforms. The participants of this qualitative study were eighteen sixth-semester students from two creative writing classes. The data were collected from participants’ writing products, namely short stories and poems. The works were uploaded to participants’ various digital platforms, then with a questionnaire to unveil their inspiration, intentions, and reasons for choosing the digital platform. There are four main findings that cover participants’ creative writing topics, writing resources, writing intentions, and social media platforms that are mostly used. The first finding highlights how technological advancement is used to abuse the power and the culture that endangered the environment. Next, the resources of their digital writing products are taken from their personal experiences, their observation, and inspired by other creative works. The third finding unveils participants’ writing intention, which are to raise awareness, express emotions, and affirm their cultural belonging. The last finding shows the choice of digital platforms, such as Instagram, TikTok, X, Medium, and Wattpad, which also reflects how the participants curate their digital identities. Furthermore, this study concludes that EFL Creative Writing in digital platforms enables the participants to express their ideas and feelings without being judged by others while at the same time they can negotiate and express evolving digital identities.